Effectiveness of Information Media on Anemia Knowledge and Compliance with Blood Increasing Tablets Consumption in Adolescent Girls: Systematic Review - Darsono, Filla Alfazriani; Hidayat, Asri (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Many young women are affected by anaemia, a health issue that is prevalent worldwide. Adolescent females are ten times more susceptible to anaemia due to their tendency to disregard their health issues, which leads to a significant number of anaemia cases each year. In order to prevent anaemia, it is imperative to disseminate information through effective information media, including booklets, pamphlets, and video media. To increase the awareness of the significance of consuming blood-increasing medications and to increase the knowledge of young women. The objective of this investigation is to ascertain the efficacy of disseminating information media regarding awareness of anaemia and adherence to the consumption of Blood Increasing Tablets among young women. The research design employed is Scoping Review. A scoping review is a preliminary step in the process of conducting a systematic review, which is designed to identify the categories of evidence that are currently available on the subject matter. They employed the PRISMA-ScR framework to conduct a search for articles in pertinent databases. The study demonstrated that the provision of information media, including leaflets and videos, substantially increased the adherence of young women to the consumption of Blood Increasing Tablets and their understanding of anaemia. Video media is the most effective category of information media intervention in terms of increasing the knowledge and consumption of Blood Tablets.